The analyzing the role of electric vehicles in urban logistics: A case of China - Yan, Zhu; Ding, Huiping; Chen, Lu (Frontiers in Environmental Science, 2023)
In recent years, the rapid development of electric vehicles has gained widespread attention, especially brought new vitality to the fast-growing logistics service industry. Electric vehicles in urban logistics are not only ideal transportation tools but also don’t affect the environment. This paper thus implements the economic valuation of electric vehicle in urban logistics from the views of both manufacturers and business users through the investigation of the pricing mechanism and discusses the potential for improving the policymaking together with the real case in China. The net present value (NPV) approach is used to quantitatively analyze the investment decisions of urban logistics electric vehicles, with government regulation and incentive policy and carbon emission trading taken into consideration. Our findings provide insights concerning the decision-making mechanism for commercializing electric vehicles in urban logistics that involves optimizing the government subsidy and transaction price between the manufacturers and business users. The results imply that, with rationalized government policy incentives and coordinated transaction price, both the manufacturer and business users are expected to achieve their break-even in limited time periods; the carbon cap placed on business users rather than manufacturers would be relatively more conducive to the marketization process.